Effect of Aloe Vera Whole Leaf Extract on Lipid Profile Status in High Fat Diet and Low Dose Streptozotocin Induced Type 2 Diabetic Rats (Medical Forum Monthly, 2024)
Objective To determine the effect of Aloe vera whole leaf extract on lipid profile in type 2 diabetic rats.Study Design: Randomized control trailPlace and Duration of Study: This study was conducted at the Department of Physiology Army Medical College, Rawalpindi in collaboration with National Institute of Health (NIH) Islamabad from April 2009 to Oct 2010.Materials and Methods: Type 2 DM was induced in 45 healthy rats by feeding high fat diet for 2 weeks and injecting a low dose (35mg/kg) of streptozotocin intra peritoneally. Type 2 diabetic rats were randomly divided into three groups, each group having 15 rats and were labeled as diabetic group, Aloe vera group and rosiglitazone group. The diabetic group was injected normal saline, Aloe vera group was treated with Aloe vera whole leaf extract in dose of 300mg/kg body weight and rosiglitazone group was given 5mg/kg body weight of rosiglitazone I/P for 21 days.Results: A significant reduction resulted in triglycerides (50%), total cholesterol (49%), low density lipoprotein (57%),, very low density lipoprotein (50%), and increase in high density lipoprotein (50%). The results of present study provide a scientific basis of using Aloe vera whole leaf extract as lipid lowering drug to reduce the complication and mortality associated with DM. Conclusion: The maximum impact was recorded in rosiglitazone group followed by Aloevera group